Subcellular extraction and enzyme characterisation of polyphenol oxidase and peroxidase in Cinnamon myrtle - Sommano S. (2017)
© 2016, Franciszek Górski Institute of Plant Physiology, Polish Academy of Sciences, Kraków. Polyphenol oxidase (PPO) and peroxidase (POD) from Backhousia myrtifolia leaf and floral tissues were characterised. PPO from both tissues showed maximum activity at pH 6.0 and 10.0 at 25 °C, whereas POD activity optima were at pH 5.0 and 9.0 at 25 °C for leaf tissues. The same pH optima for POD activity were evident at 20 °C for floral tissues. With regard to substrate specificity, B. myrtifolia PPOs were of both monophenolase (tyrosine) and diphenolase (l-DOPA) types. POD activity was highest when catechol was used as a substrate for oxidisation. K m ranged from 0.6 to 1.0 mM with l-DOPA as the substrate for PPO, and from 0.1 to 0.4 mM with H 2 O 2 and constant catechol (10 mM) as substrates for POD. In both tissues types, glutathione was a non-competitive inhibitor to PPO at the lower concentrations of 0.1–1 mM, but was uncompetitive at the higher concentrations of 10.0 mM. Sodium azide at concentrations ranging from 0.005 to 0.5 mM was a competitive inhibitor to POD. Subcellular extraction methods showed that PPO and POD were localised in the membrane fraction. Cationic native PAGE performed for both enzymes was only able to detect PPO activity. Using Western blot analyses, low molecular weight PPO isozymes from leaf tissue were identified ( < 10 kDa). Five POD isozymes (20–80 kDa) were detected in both tissue types. These ‘isoform’ patterns were investigated by two-dimensional gel electrophoresis (2DGE). PPOs were mainly neutral (pI 6–7), while POD isoforms had acidic, neutral and alkaline forms.